Anakinra and related drugs targeting interleukin-1 in the treatment of cryopyrin- associated periodic syndromes - Bachove I (Dove Medical Press, 2014)
Inessa Bachove,1 Christopher Chang2 1Cooper University Hospital, Children's Regional Hospital, Camden, NJ, USA; 2Division of Allergy and Immunology, Thomas Jefferson University, Wilmington, DE, USA Abstract: Anakinra is an interleukin (IL) receptor antagonist that works by blocking the biological activity of IL-1 by competitively inhibiting binding of IL-1 to the type 1 interleukin receptor. IL-1 production is induced in response to inflammatory stimuli and mediates various physiological mechanisms, including inflammation and immunological reactions. Patients with neonatal onset multisystem inflammatory disease (NOMID) produce excess IL-1β, a major proinflammatory cytokine that regulates innate immune responses. Anakinra binds competitively and this results in a rapid reduction in disease severity. NOMID, also known as chronic infantile neurologic, cutaneous, articular syndrome, is the most severe clinical phenotype in the spectrum of cryopyrin-associated periodic syndromes. It is characterized by cutaneous symptoms, arthropathy, and central nervous system involvement. Extensive studies in patients with NOMID have led to advances in characterizing the extent of organ-specific involvement and damage that occurs with chronic overproduction of IL-1β. NOMID is caused predominantly by mutations in the NLRP3/CIAS1 gene that encodes for the protein cryopyrin, leading to activation of the “NLRP3 inflammasome complex”. This in turn regulates the maturation and secretion of the inflammatory cytokine, IL-1β. The clinical value of IL-1β has been demonstrated by the positive response of patients after treatment with anakinra, with rapid improvement in clinical symptoms, markers of inflammation, and a significant decrease in major organ manifestations. Keywords: neonatal onset multisystem inflammatory disease, chronic infantile neurologic, cutaneous, arthritis syndrome, NLRP3, CIAS1, interleukin-1β